Measurement of the total cross section from elastic scattering in pp collisions at √ s = 8 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physics letters, 2016)
A measurement of the total pp cross section at the LHC at s=8 TeV is presented. An integrated luminosity of 500 μb−1 was accumulated in a special run with high-β⋆ beam optics to measure the differential elastic cross section as a function of the Mandelstam momentum transfer variable t. The measurement is performed with the ALFA sub-detector of ATLAS. Using a fit to the differential elastic cross section in the −t range from 0.014 GeV2 to 0.1 GeV2 to extrapolate t→0, the total cross section, σtot(pp→X), is measured via the optical theorem to beσtot(pp→X)=96.07±0.18(stat.)±0.85(exp.)±0.31(extr.)mb, where the first error is statistical, the second accounts for all experimental systematic uncertainties and the last is related to uncertainties in the extrapolation t→0. In addition, the slope of the exponential function describing the elastic cross section at small t is determined to be B=19.74±0.05(stat.)±0.23(syst.)GeV−2.
Gesehen am 12.05.2020
Im Titel steht der Buchstabe s unter dem Wurzelzeichen
The ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2829 weitere Personen]